OPTIMIZATION OF THE DIAGNOSTIC AND TREATMENT ALGORITHM FOR ACUTE ADHESIVE SMALL BOWEL OBSTRUCTION - Djuraeva Zilola Aramovna; Choriev Khaitmurod Kultura ugli; Mustafakulov Ishnazar Boynazarovich (Research Focus International Scientific Journal, 2026)
Acute adhesive small bowel obstruction (ASBO) remains one of the most common causes of emergency hospitalization in abdominal surgery and is characterized by a high risk of intestinal ischemia and postoperative complications. To evaluate the effectiveness of an optimized diagnostic and treatment algorithm in patients with ASBO. An analysis of treatment outcomes for patients with ASBO was conducted, including clinical assessment, laboratory parameters, instrumental methods (X-ray, ultrasound, CT as indicated), and dynamic observation during the first hours of hospitalization. Criteria for selecting a conservative approach and indications for early surgical intervention were developed. Application of the algorithm has improved the accuracy of early detection of complicated forms of obstruction, reduced the time to surgical decision-making, and reduced the incidence of postoperative complications. The optimized algorithm enables a rational choice of treatment tactics and contributes to improved clinical outcomes in patients with ASBO.